Connecting glass-forming ability of binary mixtures of soft particles to equilibrium melting temperatures - Yunhuan Nie (Nature Portfolio, 2020)
Glass-forming ability is an important parameter for manufacturing glassy materials, but it remains challenging to be characterized due to its nonequilibrium nature. Nie et al. provide a solution by linking it to the pressure dependence of melting temperature of constituent components in binary mixtures.